Positive Mental Health Literacy: A Concept Analysis - Carvalho, Daniel; Sequeira, Carlos; Querido, Ana; Tomás, Catarina; Morgado, Tânia; Valentim, Olga; Moutinho, Lídia; Gomes, João; Laranjeira, Carlos (Frontiers in Psychology, 2022)
Background: The positive component of Mental Health Literacy (PMeHL) refers to a person’s awareness of how to achieve and maintain good mental health. Although explored recently, the term still lacks a clear definition among healthcare practitioners. Aim: To identify the attributes and characteristics of PMeHL, as well as its theoretical and practical applications. Methods: Literature search (using the Medline and CINAHL databases) and review, covering the last 21 years, followed by concept analysis according to the steps described by Walker and Avant (2019). Results: PMeHL is considered one component of MHL, integrating positive mental health. The concept’s attributes include: a) competence in problem-solving and self-actualization; b) personal satisfaction; c) autonomy; d) relatedness and interpersonal relationship skills; e) self-control; and, f) prosocial attitude. Four case scenarios (model, borderline, related and contrary cases) were used to clarify the antecedents (individual factors and social/contextual factors) and consequences (individual sphere; relational/social sphere; contextual/organizational sphere) of PMeHL. Conclusion: PMeHL is considered a component of MHL, which deserves attention throughout the lifespan, in different contexts and intervention levels. Considering PMeHL as a multi-faceted and dynamic construct will help understand the mechanisms that improve mental health and promote healthy behaviours. Priority should be given to robust primary research focused on nursing interventions that enhance and sustain PMeHL in people and families.